Predictors of betel quid chewing behavior and cessation patterns in Taiwan aborigines - Lin, Chin-Feng (BioMed Central, 2006)
BACKGROUND: Betel quid, chewed by about 600 million people worldwide, is one of the most widely used addictive substances. Cessation factors in betel quid chewers are unknown. The present study explores prevalence and the quit rate of betel quid chewing in Taiwan aborigines. Our goal was to delineate potential predictors of chewing cessation. METHODS: A stratified random community-based survey was designed for the entire aborigines communities in Taiwan. A total of 7144 participants were included between June 2003 and May 2004 in this study. Information on sociodemographic characteristics, such as gender, age, obesity, education years, marital status, ethnicity, and habits of betel quid chewing, smoking and drinking was collected by trained interviewers. RESULTS: The prevalence of betel quid chewers was 46.1%. Betel quid chewing was closely associated with obesity (OR = 1.61; 95% CI: 1.40–1.85). Betel quid chewers were most likely to use alcohol and cigarettes together. Quit rate of betel quid chewers was 7.6%. Betel quid chewers who did not drink alcohol were more likely to quit (OR = 1.89; 95% CI: 1.43–2.50). Alcohol use is a significant factor related to cessation of betel quid chewing, but smoking is not. CONCLUSION: Taiwan aborigines have a high prevalence of betel quid chewers and a low quit rate. Alcohol use is strongly association with betel quid chewing. Efforts to reduce habitual alcohol consumption might be of benefit in cessation of betel quid chewing.